2021
DOI: 10.4025/actasciagron.v43i1.50997
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in and antioxidant activity of camu-camu fruits harvested at different maturation stages during postharvest storage

Abstract: The present study was carried out to evaluate the antioxidant activity of and the content of bioactive compounds in camu-camu fruits harvested at different maturation stages and stored. The fruits were harvested in the municipality of Cantá, Roraima State, Brazil. The experimental design was completely randomized, with three replications, in a factorial arrangement consisting of three different maturation stages (immature, semi-mature and mature) and eight days of storage (3 x 8). The fruits were analysed ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…6.00 to 1.00 mg/100 g in the peel and from ca. 300 to 133 μg/100 g in the pulp . The same studies showed that, although no yellow color was visually detected in the camu camu peel, carotenoids were present in the fruit .…”
Section: Main Groups Of Biofunctional Compounds Of Camu Camumentioning
confidence: 79%
See 3 more Smart Citations
“…6.00 to 1.00 mg/100 g in the peel and from ca. 300 to 133 μg/100 g in the pulp . The same studies showed that, although no yellow color was visually detected in the camu camu peel, carotenoids were present in the fruit .…”
Section: Main Groups Of Biofunctional Compounds Of Camu Camumentioning
confidence: 79%
“…These results showed higher antioxidant activity values compared to other fruits, such as maqui ( Aristotelia chilensis ) (6.76 ± 0.25 mmol Trolox/100 g), papaya ( Carica papaya ) (4.41 ± 0.28 mmol Trolox/100 g), and noni ( Morinda citrifolia ) (3.71 ± 0.17 mmol Trolox/100 g) for the DPPH method, as well as açaí ( Euterpe oleraceae ) (64.5 ± 19.2 μmol Trolox/g), acerola ( Malpighia emarginata ) (953 ± 34.1 μmol Trolox/g), jaboticaba ( Eugenia jaboticaba ) (317 ± 2.7 μmol Trolox/g), and Jambolão ( Syzygium cumini ) (125 ± 10.8 μmol Trolox/g) for the ABTS method . Data has shown that the antioxidant activity of camu camu tends to increase with maturity, presenting the highest values at the mature and semimature stages. , Generally, this activity has been attributed to the vitamin C and phenolic compounds of camu camu, as they can scavenge free radicals and reduce transition metals. ,,, In vivo studies showed that consuming frozen pulp extracts of camu camu significantly increased plasma antioxidant activity in Type 1 diabetic rats . Recent in vivo reports indicated a synergistic effect between bioactive compounds in camu camu (phenolic compounds, carotenoids, and vitamin C), generating a scavenging action against reactive oxygen species (ROS), for future antigenotoxic and antimutagenic effects as it was evidenced in rats …”
Section: Biofunctional Properties Of Camu Camu With Health Benefitsmentioning
confidence: 83%
See 2 more Smart Citations
“…The range reported here was also lower than the range of values, 0.74-4.71 mg QECgG 1 DW, reported by Khatana et al 30 in peel extract of different cucurbits. The low content of flavonoids recorded is largely due to the state of maturity of the melon fruits since according to Grigio et al 31 the behaviour of the flavonoid contents shows a directly proportional relationship with the state of maturation of the fruits, that is, the more mature the fruits of Camu-camu [Myrciaria dubia (Kunth) McVaugh], the higher the flavonoid content.…”
Section: Discussionmentioning
confidence: 99%